Gay Men and the Left in Post-War Britain: How the Personal Got Political - Maynard, Steven (Labour / Le Travail, 2008)
The article reviews the book, "Gay Men and the Left in Post-War Britain: How the Personal Got Political," by Lucy Robinson.
Keywords: BOOKS – Reviews; GAY Men & the Left in Post-War Britain: How the Personal Got Political (Book); GAY people; Nonfiction; ROBINSON; Lucy